2021
DOI: 10.1002/csc2.20472
|View full text |Cite
|
Sign up to set email alerts
|

Winter cereal responses to dose and application timing of trinexapac‐ethyl

Abstract: Trinexapac-ethyl (TE) is a plant growth regulator commonly used in cereal production systems. It retards plant growth by inhibiting gibberellin (GA) biosynthesis, thereby reducing the risk of stem lodging. Lodging at the latter stages of crop development can compromise grain yield and quality. Thus, application of TE may protect yield and quality in winter cereals. A field study was conducted from 2014 to 2017 across the Canadian Prairies to determine the effects of TE dose and application timings on lodging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…The variation between genotypes found in this study for the variables was also reported by Subedi et al (2021), where they evaluated the effects of TE on the agronomic characters of winter cereal species, reporting that although the effects were verified in all cultivars of the species used in the study, there were variations between genotypes for the same variable, as highlighted by plant height, number of panicle per unit area; such occurrence was justified due to the intrinsic characteristics of each genotype, such as height and yield potential. The justification adopted by…”
Section: Resultssupporting
confidence: 88%
“…The variation between genotypes found in this study for the variables was also reported by Subedi et al (2021), where they evaluated the effects of TE on the agronomic characters of winter cereal species, reporting that although the effects were verified in all cultivars of the species used in the study, there were variations between genotypes for the same variable, as highlighted by plant height, number of panicle per unit area; such occurrence was justified due to the intrinsic characteristics of each genotype, such as height and yield potential. The justification adopted by…”
Section: Resultssupporting
confidence: 88%
“…Studies that find that TE reduces lodging also find that TE reduces plant height (Subedi et al, 2021;Wiersma et al, 2011). Here, we also find that TE reduced plant height, but only in the environments where TE also reduced lodging (Figure 1B;Winchester 2020 and2021). TE also significantly increased SF r at Winchester in 2020 (3.8 vs. 4.7; Table S2).…”
Section: Effect Of Trinexapac-ethyl (Te) and N Rate Interactionssupporting
confidence: 71%
“…As opposed to yield, North American studies detect a more consistent effect of TE on lodging (Swoish & Steinke, 2017; Wiersma et al., 2011). Studies that find that TE reduces lodging also find that TE reduces plant height (Subedi et al., 2021; Wiersma et al., 2011). Here, we also find that TE reduced plant height, but only in the environments where TE also reduced lodging (Figure 1B; Winchester 2020 and 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This supposed damage to seed vigour can also reduce seed germination, plant stand and plant tillering, which then usually reduces grain yield. The adverse action of TE on modern wheat genotypes is currently under study in temperate regions such as North America (Subedi et al, 2021). However, we are not aware of previous studies evaluating TE damage to spring wheat grown in Brazil or in other tropical countries.…”
Section: Introductionmentioning
confidence: 99%